Analysis of the situation in the Light Industry in Russia - A G Litvinova (RUDN Journal of Economics, 2014)
This article analyzed the situation in the light industry in Russia in terms of integration into the world economy and the causes of its underdevelopment such as: lack of own raw materials, poor funding and support from the state, low competition, illiteracy managers in the industry. Purpose of the research was to identify the factors that negatively influence the development of the industry and the development of effective tools for gaining its stable positions in both domestic and foreign markets.